The complete Google Go programming course for beginners - Valentine, Dave (Packt Publishing, 2017)
"Our goal for you in this course is: For you to become a beginner Ninja in one of the hottest new languages called "Google Go" and also known as Golang. Google go is taking the development world by storm, because of its system level access and its design which gives programmers the ability to create multi-core programs. This is the first development language really developed for the type of multi-core CPU computers that have been in the market for the last ten years. Created by three genius developers are Google - to solve deficiencies Google was experiencing with conventional computer languages. This course is especially structured to solve a number of problems that introductions to programming languages suffer form."--Resource description page